tanα+tanβ=tan(α+β)-tanαtanβtan(α+β)证明
1个回答
tan(A+B)=(tanA+tanB)/(1-tanAtanB)
给式子右边提出tan(α+β),即
tanα+tanβ=(1-tanAtanB)×tan(α+β)
相关问题
tan(α±β)=(tanα±tanβ)/(1±tanαtanβ)的变式tanαtanβtan(α+β)=tan(α+β
证明:sin(α+β)/cos(α-β)=tanα+tanβ/1+tanαtanβ
简单的高一三角函数证明题证明:tanα+tanβ=tan(α+β)-tanαtanβtan(α+β)
α+β=45度,则tanα+tanβ+tanαtanβ=?
cos(α+β)/cos(α-β)=(1-tanαtanβ)/(1+tanαtanβ)的推导
证明(要过程):1.(tan(α+β)-tanα)/(1+tanαtan(α+β))=sin2β/2cos平方β
已知tanα+tanβ=2,tan(α+β)=4,tanα
tan(α+β)=2,tanβ=-3,则tanα=
两角和与差的正切公式的变形形式tan(α+β)=(tanα+tanβ)/(1-tanα ·tanβ) tan(α-β)=